2023
DOI: 10.1215/00703370-10878053
|View full text |Cite
|
Sign up to set email alerts
|

How Education Shapes Women's Work and Family Lives Across Race and Ethnicity

Abstract: Drawing on life course and intersectional approaches, this study examines how education shapes the intertwined domains of work and family across race and ethnicity. By applying multichannel sequence analysis and cluster analysis to the National Longitudinal Survey of Youth 1979, we identify a typology of life course trajectories of work and family and test for the interactive associations of race and ethnicity with college education for different trajectory types. While our results show statistically significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…As noted above, difficulties in balancing caregiving needs with other responsibilities may adversely affect the employment and income of the parents of a child with a health condition, which could lead to financial strain that exacerbates their stress. Previous literature has found that parents' opportunities to combine family and work are likely to be shaped by their educational level (Pessin, Damaske, and Frech 2023), as education is related to both job demands and flexibility, which are known to affect work-family balance among parents of sick children (Brown and Clark 2017;Hjelmstedt et al 2021;Kish, Haslam, and Newcombe 2020).…”
Section: The Moderating Impact Of Parental Educationmentioning
confidence: 99%
“…As noted above, difficulties in balancing caregiving needs with other responsibilities may adversely affect the employment and income of the parents of a child with a health condition, which could lead to financial strain that exacerbates their stress. Previous literature has found that parents' opportunities to combine family and work are likely to be shaped by their educational level (Pessin, Damaske, and Frech 2023), as education is related to both job demands and flexibility, which are known to affect work-family balance among parents of sick children (Brown and Clark 2017;Hjelmstedt et al 2021;Kish, Haslam, and Newcombe 2020).…”
Section: The Moderating Impact Of Parental Educationmentioning
confidence: 99%